Aesthetics of futures. Shaping shared visions of tomorrow. (28th July 2017) - Celi, Manuela; Formia, Elena
Abstract: Designers – as futurists – by participating in the building of the future, create new levels of value with the motivation to fulfil the unmet needs and desires of people. Overstepping the private mission, design, such as other creative fields (cinema, literature, art, photography, etc.), creates utopian or dystopian narrations, exploring the dimension of public exhibition, involvement and empowerment. Starting from these premises after a short introduction on the relationship between design and humanities the paper pays special attention to the fictionary role of design. The paper will present the importance of design in the debate about "Future Literacy" introducing the notion of design fiction though a reading of the evolution of the respective theoretical framework. Finally, the authors will analyse the case-study of the designer and artist Karolina Sobecka introducing a reflection on the aesthetics of design fictions and on the value of design in the practice of sharing futures.